On eating insects - Evans, Josh; Flore, Roberto; Frøst, Michael Bom (Phaidon Press Limited, 2017)
The concept of eating insects has taken off in recent years in the West, with media coverage ranging from sensationalist headlines to passionate press pieces about the economic and nutritional benefits. Yet little has been written about how they taste, how diverse they are as ingredients, and how to prepare them as food. On Eating Insects is the first book to take a holistic look at the subject, presenting thought-provoking essays on the cultural, political and ecological significance of eating insects, alongside fascinating stories from the authors' field trips around the world (honey ants in Australia, lake flies in Kenya, giant hornets in Japan) and detailed tasting notes. The exquisite recipes are sophisticated, surprising and will make you think of eating insects in a whole new way....COVER.
Titelzusatz auf Umschlag: essays, stories and recipes
Keywords: Cooking (Insects) / fast / (OCoLC)fst01753133; Edible insects / fast / (OCoLC)fst00902445; Entomophagy / fast / (OCoLC)fst00912768; Sustainability / fast / (OCoLC)fst01747391; Entomophagy; Edible insects; Cooking (Insects); Sustainability; Insekten; Lebensmittel